Short-Term Effects of Wood Biochar on Soil Fertility, Heterotrophic Respiration and Organic Matter Composition - Rossella Curcio; Raffaele Bilotti; Carmine Lia; Michele Compitiello; Silvana Cangemi; Mariavittoria Verrillo; Riccardo Spaccini; Pierluigi Mazzei (Agriculture)
Biochar may represent a sustainable and eco-friendly strategy to recycle agroforestry wastes, sequester carbon and improve soil health. With the aim of proving these benefits in a real scenario, we treated several soil parcels with 0 (CTRL), 1 (LOW) and 3 (HIGH) kg/m2 of wood biochar, in open-field trials. The heterotrophic soil respiration (SR) was monitored continuously for two months via a Closed Dynamic Chamber (CDC) associated with an innovative pilot system, and the most important soil chemical parameters were measured 9 and 54 days after biochar application. Biochar induced an immediate dose-dependent increase in organic matter content and CEC (up to 41.6% and 36.8% more than CTRL, respectively), which tended to slightly and gradually decrease after 54 days. In all cases, biochar induced a more pronounced SR, although the most enhanced microbial response was detected for the LOW parcel (19.3% higher than CTRL). Fennels were grown in treated soils and only LOW microplots gave a significantly better response (weight and size). Finally, NMR, FT-IR and Pyr-GC/MS analyses of LOW SOM extracts revealed a relevant impact on the composition, which was accompanied by a higher content of carbohydrates, indole-based compounds and FAME species correlating with enhanced microbial activity. Our findings demonstrate that the proper biochar dose improves soil fertility by creating an environment favorable to plants and promoting microbial activity.